Implementasi Pembelajaran Aktif di Sekolah Tahfizh Kiswah Kontribusi Mahasiswa Tarbiyah Prodi MPI dan PGMI - Ilhamsyah, Rizal; muji, muji; khairunnisa, salsabila; batubara, bitcar (Jurnal Likhitaprajna, 2024)
The implementation of active learning at the Tahfizh Kiswah School aims to increase student involvement in memorising the Qur'an. The contribution of Tarbiyah students of the MPI and PGMI Study Programs in this service is in the form of the application of interactive and active participation-based learning methods, such as group discussions, role plays, and project-based learning. This method is expected to accelerate the process of memorisation, and students' understanding of the verses taught. Active learning is expected to increase student motivation, reduce boredom, and deepen understanding of the meaning of the Qur'an. The results of this service show that students are more active in participating in learning activities, thereby improving the quality of teaching at the Tahfizh Kiswah School. With the application of this method, it is hoped that a more fun and productive learning atmosphere can be created, as well as strengthen students' skills in memorising the Quran.